Crude Glycerol Hydrogenolysis to Bio-Propylene Glycol: Effect of Its Impurities on Activity, Selectivity and Stability - Gatti, Martin Nicolas (2023)
The wide availability of crude glycerol and its low market price make this by-product ofthe biodiesel industry a promising raw material for obtaining high-value-added products throughcatalytic conversion processes. This work studied the effect of the composition of different industrialcrude glycerol samples on the catalytic hydrogenolysis to 1,2-propylene glycol. A nickel catalystsupported on a silica?carbon composite was employed with this purpose. This catalyst proved tobe active, selective to 1,2-propylene glycol and stable in the glycerol hydrogenolysis reaction in theliquid phase when analytical glycerol (99% purity) was employed. In order to determine the effect ofcrude glycerol composition on the activity, selectivity and stability of this catalyst, industrial crudeglycerol samples were characterized by identifying and quantifying the impurities present in them(methanol, NaOH, NaCl and NaCOOH). Reaction tests were carried out with aqueous solutions ofanalytical glycerol, adding different impurities one by one in their respective concentration range.These results allowed for calculating activity factors starting from the ratio between the rate ofglycerol consumption in the presence and in the absence of impurities. Finally, catalyst performance was evaluated employing the industrial crude glycerol samples, and a kinetic model based on the power law was proposed, which fitted the experimental results taking into account the effect of glycerol impurities. The fit allowed for predicting conversion values with an average error below 8%.